Decoding the correlation between heart activation and walking path by information-based analysis - Kamal, Shahul Mujib; Babini, Mohammad Hossein; Tee, Rui; Krejcar, Ondrej; Namazi, Hamidreza (Technology and health care, 2023)
BACKGROND: One of the important areas of heart research is to analyze heart rate variability during (HRV) walking. OBJECTIVE: In this research, we investigated the correction between heart activation and the variations of walking paths. METHOD: We employed Shannon entropy to analyze how the information content of walking paths affects the information content of HRV. Eight healthy students walked on three designed walking paths with different information contents while we recorded their ECG signals. We computed and analyzed the Shannon entropy of the R-R interval time series (as an indicator of HRV) versus the Shannon entropy of different walking paths and accordingly evaluated their relation. RESULTS: According to the obtained results, walking on the path that contains more information leads to less information in the R-R time series. CONCLUSION: The analysis method employed in this research can be extended to analyze the relation between other physiological signals (such as brain or muscle reactions) and the walking path.
Keywords: elektrokardiografie; R-R interval time series; entropie; Shannon entropy; Time Factors; srdeční frekvence; časové faktory; Electrocardiography; Heart Rate Variability (HRV); lidé; information content; walking path; Heart Rate; Walking; chůze; Entropy; Humans